The affect of temperature to water content determination for hua hin soil - คีรีรัตน์, ชูศักดิ์ (Frontiers in Engineering Innovation Research, 2006)
Water content is the important basic property of geotechnical engineering. It could be tested from several methods. The popular is oven dry method which is a standard one and accepted in overall. This method uses standard temperature of 105[plusmn]5 Celsius Degree to dried of soil not less than 16 hours . In this study. it used varied temperature at 105, 125, 150, 175, 200 and 220 Celsius Degree to dried of HUA HIN soil. The samples in this study are 621 samples of HAU HIN soil in 50 areas. From the conclusion found that relationship of ash content and water content is linear correlation and has coefficient of correlation equal I of linear regression. In addition. Relationship of water content and temperature arc divided as 7 groups depend on closely of water content. From evaluation able to construct adjusted factor curve for determined correct water content when temperature testing more than 105 degree Celsius was shown in conclusion. The benefit of this study is a time saving in water content determination by oven dry method.